PKM Penguatan Kapasitas Guru dalam Implementasi Kurikulum Sekolah Ramah Anak Berbasis Budaya Positif di Lingkungan Belajar - Siti Raihan; Saprizal; Fitriana; Awayundu Said; Amir Pada (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to strengthen the capacity of teachers at SD Inpres Timbuseng in implementing a Child-Friendly School (CFS) curriculum based on a positive school culture. The program was initiated in response to preliminary findings showing that teachers had not fully understood the principles of CFS, had yet to apply empathetic communication, and had not integrated positive values into their teaching materials. The program was carried out using a transformative participatory approach through four stages: needs identification, training and workshops, implementation assistance, and reflective evaluation. One of the main approaches introduced was positive discipline, a pedagogical strategy that emphasizes dialogue, appreciation, and logical consequences to build a non-violent, positive school culture. The program results showed a significant improvement in teachers’ understanding of the CFS curriculum (from 62.5% to 88.3%), the development of child-friendly teaching materials, and changes in classroom teaching practices through the implementation of positive discipline supported by empathetic and reflective communication strategies. Teachers actively participated in all stages of the program, and the principal provided full support for its implementation. The program has implications for improving the quality of inclusive and participatory learning environments and opens opportunities for replication and further development through teacher learning communities and supportive school policies. Thus, this PKM program makes a concrete contribution to the creation of child-friendly schools.